Evaluation of the effects of curcumin on chronic obstructive pulmonary disease with a bio-computational approach - Maboudian, Mohammad; Amjad, Elham; Asnaashari, Solmaz; Dastmalchi, Siavoush; Sokouti, Babak; Javadzadeh, Yousef (Egyptian Journal of Medical Human Genetics, 2024)
Background According to the increasing trend of COPD, the timely diagnosis and treatment of the disease can reduce the high costs to the health systems. Therefore, by biological calculation methods, signaling pathways and genes involved in this disease can be obtained and used to design drugs and other treatment methods. By using biological calculations, we determined that curcumin can affect this disease and its genes and signaling pathways. Our goal in this study was to find the genes by which curcumin exerts its effect and can maintain the function of corticosteroids against oxidizing agents. Results By finding the genes, it is possible to find precisely the pathways by which curcumin works, which can be used to design other drugs that cause these pathways and minimize their side effects. This study considers healthy samples (with/without curcumin) and oxygen-free radicals (with/without curcumin). Finally, statistical algorithms extract meaningful genes as effective biomarkers to investigate curcumin's effects and signaling pathways in COPD. The results show that the genes finally obtained as the most critical genes confirmed by the literature are effective in COPD. Finally, curcumin was input in SwissTargetPrediction to identify potential protein receptors. We used LigPlot+ software to visualize the receptor–ligand binding result provided by iGEMDOCK. Conclusions The data showed that the most significant genes in each group have been confirmed in other studies to be effective in this disease, and protein–protein interaction networks can be established between them to investigate their roles.